2020
DOI: 10.18470/1992-1098-2020-1-130-136
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ecotoxicity of Nanoparticles of Cobalt, Copper, Nickel and Zinc Oxides on Biological Indicators of the State of Ordinary Chernozem

Abstract: Академия биологии и биотехнологий им. Д.И. Ивановского, Южный федеральный университет, Ростов-на-Дону, Россия Контактное лицо Сергей И. Колесников, доктор сельскохозяйственных наук, профессор, заведующий кафедрой экологии и природопользования Академии биологии и биотехнологий им. Д.И. Ивановского, Федеральное государственное автономное образовательное учреждение высшего образования «Южный федеральный университет»; 344090 Россия, г. Ростов-на-Дону, пр. Стачки, 194/1. Тел.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Laboratory studies of biological indicators were performed using methods (Table 1). It was efficient to use sensitive biological indicators to diagnose soil conditions after chemical pollution [43,46,47]. The used set of indicators gave an informative estimate of the biological processes taking place in the soil and the ecological state of the ground.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…Laboratory studies of biological indicators were performed using methods (Table 1). It was efficient to use sensitive biological indicators to diagnose soil conditions after chemical pollution [43,46,47]. The used set of indicators gave an informative estimate of the biological processes taking place in the soil and the ecological state of the ground.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…In this case, positively charged particles that easily cross cellular barriers and bind to DNA are the most toxic particles [18]. In particular, chernozems contaminated with UFP Co 3 O 4 are characterized by a decrease in the total number of bacteria, especially the activity of catalase and dehydrogenases [19], and in the freshwater microalga Chlorella minutissima, with similar contact, the growth and synthesis of chlorophyll in cells slow down. Moreover, the effective EC 50 concentrations identified in this case are consistent with those obtained in experiment I and amount to 38.16 ± 1.99 mg/L (≈4.8 × 10 -4 mol/L) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a great number of works is devoted studying the toxic effect of metal nanoparticles on soil, plants and microbiota 9,10 . Kolesnikov with colleagues 11 revealed that the nanopowders of Co3O4, CuO, NiO and ZnO exert the strongest effect on the microbiological parameters of chernozem in comparison with the "ordinary" forms of oxides. The absorption of nanoparticles by the soil may negatively affect the state of soil biota and plants, as its components, posing a serious risk to the environment.…”
Section: Introductionmentioning
confidence: 99%